Autistic differences in the temporal dynamics of social attention - Hedger, Nicholas (Autism, 2021)
Individuals with autism spectrum disorders typically exhibit reduced visual attention towards social stimuli relative to neurotypical individuals. Importantly, however, attention is not a static process, and it remains unclear how such effects may manifest over time. Exploring these momentary changes in gaze behaviour can more clearly illustrate how individuals respond to social stimuli and provide insight into the mechanisms underlying reduced social attention in autism spectrum disorder. Using a simple passive eye-tracking task with competing presentations of social and nonsocial stimuli, we examine the different ways in which attention to social stimuli evolves over time in neurotypical adults and adults with and autism spectrum disorders. Our temporal modelling of gaze behaviour revealed divergent temporal profiles of social attention in neurotypical and observers with autism. Neurotypical data showed an initial increase in social attention, a ‘decay’ and subsequent ‘recovery’ after prolonged viewing. By contrast, in individuals with autism spectrum disorder, social attention decayed over time in a linear fashion without recovery after prolonged viewing. We speculate that the ‘gaze cascade’ effect that maintains selection of social stimuli in neurotypical observers is disrupted in individuals with high autistic traits. Considering these temporal components of gaze behaviour may enhance behavioural phenotypes and theories of social attention in autism spectrum disorder. LAY ABSTRACT: One behaviour often observed in individuals with autism is that they tend to look less towards social stimuli relative to neurotypical individuals. For instance, many eye-tracking studies have shown that individuals with autism will look less towards people and more towards objects in scenes. However, we currently know very little about how these behaviours change over time. Tracking these moment-to-moment changes in looking behaviour in individuals with autism can more clearly illustrate how they respond to social stimuli. In this study, adults with and without autism were presented with displays of social and non-social stimuli, while looking behaviours were measured by eye-tracking. We found large differences in how the two groups looked towards social stimuli over time. Neurotypical individuals initially showed a high probability of looking towards social stimuli, then a decline in probability, and a subsequent increase in probability after prolonged viewing. By contrast, individuals with autism showed an initial increase in probability, followed by a continuous decline in probability that did not recover. This pattern of results may indicate that individuals with autism exhibit reduced responsivity to the reward value of social stimuli. Moreover, our data suggest that exploring the temporal nature of gaze behaviours can lead to more precise explanatory theories of attention in autism.